Development of Electricity Energy Meter Monitoring for Residential Purpose - Abd Rahim, Zul Farid Hakim; Mohd Zin, Rosnah (Evolution in Electrical and Electronic Engineering, 2021)
The purpose of the project is to develop an automatic load energy reading monitor that can be used on a real-time basis. Energy meter monitoring is a tool for measuring and monitoring electricity from a 230 V power source. This metering monitoring system includes a sensor that detects the blinking of an LED attached to the meter and converts it to a voltage signal. The Internet of Things (IoT) may be used to track power and bills on a daily basis using a smartphone. The problem is that at the end of each month, the household energy bill displays an additional number many times, generating consumer dissatisfaction and complaints. Because consumers are unaware of their daily energy consumption, they frequently overspend to pay their bills at the end of the month. The user may monitor and estimate the rate of energy consumption using this technology, as well as improve the amount of money saved. It is also lightweight and compact due to the usage of ESP8266 as a System on Chip (SoC) for control units. It was discovered via the project analysis that the obtained data may be used to extract the consumption pattern as well as the faults in the existing system. This project's measuring source is a house energy meter that was installed and supplied to the household. This is a good source of power to use for calculating electricity consumption.